The Effect of Yamamoto New Scalp Acupuncture Therapy on Lowering The Blood Pressure of Hypertension Patients At A Primary Care Service Family Medicine Acupuncture Clinic ''XYZ'' Jakarta - Yuliawati Kusumaningrum; Mayang Wulandari; Ikhwan Abdullah; Chantika Mahadini (Syntax Literate, 2022)
Hypertension can hinder the development of social and economic stability and can become a major threat to the structure of healthcare services. The management of hypertension cases in primary care can be performed through a family medicine approach by taking into account the potential of the family as the supporting resource and/or obstacles to the successful management of hypertension patients. This can be performed with acupuncture methods, one of which is the Yamamoto New Scalp Acupuncture (YNSA) method. Objective: To determine the effect of acupuncture therapy using YNSA method on lowering the blood pressure of patients with hypertension at the Primary Care Service Family Medicine Clinic "XYZ, Jakarta." Methods: This quantitative research uses pre-experimental and post-experimental nonrandom purposive sampling techniques which yield a total sample of 76 respondents. The sample has met certain criteria and is divided into 2 groups: the intervention group and the control group. The assessment was carried out for 7 days for each group. Conclusion: The use of the YNSA method for patients with hypertension in the two groups had significantly different results during pre- and post-treatment with p < 0.05. This shows that there is a significant difference in the two groups from the second to the seventh days.